Læring i et Vygotsky-perspektiv Muligheter og konsekvenser for opplæringen - Faldet, Ann-Cathrin (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2023)
Learning in a Vygotskian Perspective demonstrates how Lev Vygotsky's (1896-1934) socio-cultural perspectives on learning and education can in various ways hone our perceptions of good education in kindergarten and school. Vygotsky's ideas are an important frame of reference for current educational thinking and constitute a central perspective within the field of education. And yet, it is hard to ignore the pronounced difference between the socio-cultural perspective and the standardization of education occurring today, propelled globally by politicians and education reformers. This anthology contributes to a deeper understanding of how socio-cultural perspectives can provide ""opportunities and consequences for education"". The authors of the chapters in the book have been inspired in various ways by Vygotsky's pedagogical ideas, actively using and promoting them in new research projects in the context of new fields of research and practice within kindergartens, schools and teacher education. The book will be of interest to researchers, teacher educators, teachers, students and others who are interested in socio-cultural learning processes in education. The authors are affiliated with a variety of national and international institutions. The editors are affiliated with the Faculty of Teacher Education and Pedagogy at Høgskolen i Inlandet and the Department of Sámi Teacher Education at Sámi allaskuvla. Ann-Cathrin Faldet is an associate professor in pedagogy, Thor-André Skrefsrud is a professor in pedagogy, and Hege Merete Somby is an associate professor in pedagogy.